Morphosyntactic variation in Bantu: Focus on East Africa - (:unkn) unknown (My University, 2022)
Recent studies have developed a systematic approach to morphosyntactic variation among Bantu languages, taking well-known and widely attested construction types as a starting point and sketching their distribution across the family. One such approach, Guérois et al. (2017), utilises 142 morphosyntactic parameters or features, across a sample of some 50 Bantu languages (Marten et al. 2018). The present paper builds on this work and focusses on 10 parameters of variation where there is a significant difference between the values for East African Bantu languages and non-East African Bantu languages of the sample. The parameters relate to areas such as noun class morphology, agreement, and word order and so cover a wide range of morphosyntactic structures. The paper shows that the differences overall can be used for an initial characterisation of East Africa as a morphosyntactic area, with its own specific language change and language contact dynamics.
Keywords: African Research